Towards shared accountability in international human rights law : law, procedures and principles - Vandenbogaerde, Arne (Cambridge, United Kingdom ; Antwerp ; Portland : Intersentia, 2016)
"Non-State actors, principally corporations and international organizations, as well as foreign States, influence decision-making. This reality particularly affects the enjoyment and implementation of economic, social and cultural (ESC) rights. Alongside what has become a fast-moving reality, legal developments in the field of ESC rights are also happening at a fast pace. In the last decade we have not only witnessed the end of the ESC justiciability debate, including a growing recognition of these rights at the domestic level, but also the adoption of an international complaints procedure to deal with violations of ESC rights (OP-ICESCR). Yet, these legal developments fall short of providing accountability in a globalized world. There is a discrepancy between international human rights law - with its focus on the territorial State - and the current globalized context in which non-state actors and foreign States also affect the enjoyment of ESC rights. Scholars have argued for the expansion of the duty-bearer side of human rights law in order 'to synch' human rights law with reality. Most of the research in the last decade has focused on the recognition of the obligations of foreign States and NSAs, less so on subsequent rules for the attribution and distribution of obligations, responsibility, and remedies. What are the (legal) building blocks or foundations of a multi-duty-bearer accountability framework?"--Back cover.
Introduction -- The Concept of Accountability -- State Reporting Procedures at the International and Regional Level -- Individual, Collective and Inter-State Complaint Procedures in the International and Regional Accountability Framework -- Inquiry Procedures in the International and Regional Accountability Framework -- International Peer-Review Accountability Mechanisms -- Special Procedures in the International and Regional Systems -- Admissibility Criteria in a Multi-Duty Bearer Framework -- Attributing Obligations in a Multi-Duty Bearer Framework.
Based on the author's Ph. D. thesis--University of Antwerp, 2015 --Acknowledgment.
Includes bibliographical references (pages 319-349).
Keywords: International law and human rights; Non-state actors (International relations); Human rights and globalization; Liability for human rights violations; 86.81 human rights; Droits de l'homme.; Droit d'ingerence.; Organisation des Nations unies; Application des lois; Theses; Human rights and globalization; International law and human rights; Liability for human rights violations; Non-state actors (International relations); Human rights